Q for Queer? : Analysing Queerness in Star Trek in the 1980s, 1990s and 2020s - Kari, Henri (My University, 2024)
This thesis looks into the character of Q who appears in the Star Trek sci-fi franchise through queer lenses. The research material was gathered from Star Trek: The Next Generation (1987–1994) and Star Trek: Picard (2020–2023) by using close reading. Close reading was done on eight episodes of Star Trek: The Next Generation and seven episodes of Star Trek: Picard, in which Q appeared. Besides queer theory, the term of camp and previous studies around flamboyant villains were used for analysing Q. The thesis is a part of the long-lasting research into science fiction and a continuation of earlier queer analysis of the genre and more specifically, Star Trek. Besides queer research literature this thesis utilizes research of Star Trek and interviews from people associated with production of Star Trek. The main research question in the thesis is asking how Q appears in Star Trek through queer analysis by utilising previously mentioned terms. Because the thesis is analysing two television series which have been made during very different eras, the thesis is also analysing how Q as a character differs from series to series. During the thesis it becomes evident that Q fits well into queer tropes, especially when utilising camp. The character changed significantly between the 1980s and 1990s Star Trek: The Next Generation and the 2020s Star Trek: Picard. In Star Trek: Picard the character appears in a lot more serious manner, lacking the kind of camp attitude that was present in Star Trek: The Next Generation.

Tutkielma tarkastelee Star Trek scifi-universumissa esiintyvää Q-nimistä hahmoa queer- tutkimuksen avulla. Tutkimusaineisto perustuu kahteen Star Trek-sarjaan: Star Trek: The Next Generation (1987–1994) sekä Star Trek: Picard (2020–2023), joita analysoidaan lähiluvun avulla. Lähilukuun valikoitui kahdeksan Star Trek: The Next Generation -jaksoa sekä seitsemän Star Trek: Picard -jaksoa, joissa Q esiintyi. Queer-tutkimuksen lisäksi Q-hahmon analyysiin hyödynnetään camp-termiä sekä aikaisempaa tutkimusta queer-antagonisteista. Tutkimus on osa pitkäaikaista scifi-genren tutkimusta ja toimii jatkumona aikaisempiin queer-analyyseihin liittyen itse genreen ja Star Trek - universumiin. Queer-tutkimuskirjallisuuden lisäksi tutkielma hyödyntää Star Trek - universumiin liittyvää tutkimusta sekä tuotannossa olleiden ihmisten haastatteluita. Tutkielman päätutkimuskysymys keskittyy siihen, millainen hahmo Q on queer-analyysin näkökulmasta, hyödyntäen edellisessä kappaleessa mainittuja termejä. Koska tutkielma analysoi kahta televisiosarjaa, jotka ovat tuotettu hyvin eri aikoina, tutkielma analysoi myös sitä, mitä eroja Q-hahmon kuvauksessa on kussakin sarjassa. Tutkimuksessa tulee ilmi se, kuinka Q sopii vahvasti queer-kuvastoon etenkin camp-termiä hyödyntäen. Myös hahmon kuvaus 1980- sekä 1990 -luvuilla kuvatun Star Trek: The Next Generation -sarjan sekä 2020-luvun Star Trek: Picard -sarjan välillä erosi vahvasti toisistaan hahmon esiintyessä tuoreemmassa sarjassa huomattavasti totisempana hahmona ilman yhtä vahvaa camp-ilmaisua.
Keywords: queer-tutkimus, tieteissarjat, Star Trek, camp